Bayerische Pkw-Maut: Ausgangspunkt für ein modernes Preissystem - Ferdinand Dudenhöffer (Wirtschaftsdienst, 2013)
Über die Einführung einer Pkw-Maut wird nach der Bundestagswahl heftig diskutiert. Ferdinand Dudenhöffer macht den Vorschlag, die Maut zu nutzen, um damit das gesamte Verkehrssteuersystem zu modernisieren. Sowohl die Schadstoffbelastung als auch die Staugefahr könnte auf diese Weise gelenkt werden. – – Horst Seehofer, Bavaria's prime minister, seems to be close to his objective of implementing a road toll for foreign cars in Germany. As German road infrastructure suffers from large deficits, a new fiscal instrument seems to be inevitable. Thus, Seehofer's initiative points in the right direction, however, applying a suboptimal vignette model is not the right approach. The opportunity should be used to establish a toll model which creates efficient allocation and fiscal effects. This article sets out three simple principles which allow the implementation of such a system.
Keywords: L91; Q55; R41; 330; Autobahn; Straßenbenutzungsgebühr; Verkehrspolitik; Deutschland